2020
DOI: 10.14744/nci.2020.63004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of neutrophil to lymphocyte ratio in esophageal squamous cell carcinoma

Ayşegül Sakin

Abstract: OBJECTIVE: The purpose of the study was to assess the effect of neutrophil-to-lymphocyte ratio (NLR) on recurrence and survival in patients with Esophageal Squamous Cell Carcinoma (ESCC) undergoing surgery. METHODS: This was a retrospective analysis of the 80 resectable ESCC patients who underwent surgery at Yuzuncu Yil University Faculty of Medicine between 2008 and 2018. Receiver operator characteristics curve of NLR was plotted for disease-free survival (DFS). The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…24,25 The relationship between the CONUT score and the perioperative surgical risk and postoperative prognosis of malignancies such as gastric, esophageal, pancreatic, liver, cervical, and bladder cancers has been reported. [26][27][28][29][30][31] Studies have shown that the CONUT score is related to the prognosis of cancer patients receiving chemotherapy. However, its effectiveness in patients receiving ICI has not been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 The relationship between the CONUT score and the perioperative surgical risk and postoperative prognosis of malignancies such as gastric, esophageal, pancreatic, liver, cervical, and bladder cancers has been reported. [26][27][28][29][30][31] Studies have shown that the CONUT score is related to the prognosis of cancer patients receiving chemotherapy. However, its effectiveness in patients receiving ICI has not been studied.…”
mentioning
confidence: 99%
“…The Controlling Nutritional Status (CONUT), which consists of serum albumin, peripheral lymphocyte count, and serum total cholesterol, was used to assess early nutritional status 24,25. The relationship between the CONUT score and the perioperative surgical risk and postoperative prognosis of malignancies such as gastric, esophageal, pancreatic, liver, cervical, and bladder cancers has been reported 26–31. Studies have shown that the CONUT score is related to the prognosis of cancer patients receiving chemotherapy.…”
mentioning
confidence: 99%
“…We searched and summarized the literature review related to the use of IBPSs for predicting the prognosis of gastrointestinal cancers. [7][8][9][13][14][15][16][21][22][23][24][25][26][27][28][29][30] Although the results of these studies vary, the cut-off values and tendencies are generally similar (Table S2). Aside from IBPS, male sex, age ≥ 75 years, and a CEA level of > 5 were also associated with poor OS.…”
Section: Discussionmentioning
confidence: 99%
“…A study which enrolled 68 ESCC patients who underwent definitive concurrent chemoradiotherapy showed that higher posttherapy NLR was associated with poorer OS (median 9.4 vs.15.2 months, P=0.03) (29). Studies have shown that among patients with EC who underwent surgery, lower pre-treatment NLR was also associated with diseasefree survival (DFS) or OS (30)(31)(32). Moreover, a study reported that preoperative NLR was an independent variable associated with the development of postoperative complications (33).…”
Section: Discussionmentioning
confidence: 99%